Optimalisasi Gerakan Yoga untuk Mengurangi Ketidaknyamanan pada Kehamilan - Budi Rahayu; Reni Merta Kusuma; Alfie Ardiana Sari (PT FORMOSA CENDEKIA GLOBAL, 2022)
Pregnancy conditions in TM 1 to TM III will tone many problems that occur even though it is in physiological pregnancy let alone pathological pregnancy. The approach used to overcome problems in pregnancy is still widely done conventionally, therefore the management of midwifery care must be considered to reduce the discomfort of pregnant women so that pregnancy feels more comfortable, so that pregnancy becomes more pleasant and pregnant women become more productive during pregnancy. This community service aims to empower pregnant women in overcoming problems during pregnancy. The process carried out in community service is to provide information education during pregnancy and teach yoga movements